2010
DOI: 10.1088/0256-307x/27/5/057302
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Controlled Synthesis and Related Growth Mechanism of Pb(OH) 2 Nanorods by Solution-Phase Reaction

Abstract: We present a simple method to synthesize Pb(OH)2 nanorods by solution-phase reaction. Rod-like lead hydroxide precipitates are obtained by mixing lead nitrate with a concentration of about 0.01 M and potassium hydroxide with concentration of about 0.03 M in an aqueous solution. Sodium chloride as an additive is premixed with the lead nitrate aqueous solution. The presence of chloride ions in the precursor solution results in the rod-like morphology of lead hydroxide precipitates. The growth mechanism of the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It should be noted that the Dirac nodal line discovered in the previously reported 2D flat monolayer is usually protected by an in-plane mirror symmetry σ h , 47–49 which is obviously not applicable for our case in that in-plane mirror eigenvalues are the same as the two p z -induced Dirac nodal line bands. In order to fully clarify the formation of Dirac points along the high-symmetry paths K – Γ and Γ – M , we analyze the group symmetry and their eigenvalues of the two Dirac nodal line bands.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…It should be noted that the Dirac nodal line discovered in the previously reported 2D flat monolayer is usually protected by an in-plane mirror symmetry σ h , 47–49 which is obviously not applicable for our case in that in-plane mirror eigenvalues are the same as the two p z -induced Dirac nodal line bands. In order to fully clarify the formation of Dirac points along the high-symmetry paths K – Γ and Γ – M , we analyze the group symmetry and their eigenvalues of the two Dirac nodal line bands.…”
Section: Resultsmentioning
confidence: 65%
“…As one of the most active research fields, searching for preferable 2D nodal line semimetals is always ongoing. Although there are quite a few theoretical studies of 2D nodal line materials, 35,38,47–49 only Cu 2 Si and CuSe have been observed experimentally. 50,51 However, strictly speaking, Cu 2 Si and CuSe are not desirable in that their nodal loops are gapped by the sizable SOC.…”
Section: Resultsmentioning
confidence: 99%